Sustainable Valorization of Rice Straw for Bioethanol Production Using Saccharomyces cerevisiae: A Circular Bioeconomy Approach - Efrina, Efrina; Syukri, Daimon; Hamdika, W; Rozi, F; Winowatan , A; Sari, HP (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The utilization of rice straw waste as a renewable feedstock for bioethanol production presents an innovative approach to sustainable agricultural waste management and green energy development. This study aimed to evaluate the conversion process of rice straw into bioethanol through four main stages: material preparation, hydrolysis, fermentation, and distillation. One kilogram of dried rice straw was used as the primary substrate, enriched with 8% molasses and 5% Saccharomyces cerevisiae as the fermentative inoculum. Hydrolysis was conducted by boiling for 1 hour, resulting in 32.5 g/L of reducing sugars. Fermentation was performed at ambient temperature (±30°C) for 30 days, yielding an ethanol concentration of 65% (v/v) as measured by the pycnometer method, with a sugar conversion efficiency of 78%. Distillation at 78–80°C produced 250 mL of ethanol distillate from 1500 mL of fermented broth. The results indicate that rice straw has significant potential as a bioethanol feedstock, not only as an alternative renewable energy source but also as a natural solvent for applications in industries such as perfumery. This research highlights the importance of integrated rice straw valorization in reducing environmental pollution, enhancing economic value, and promoting the transition toward a circular and sustainable agricultural economy. Contribution to Sustainable Development Goals (SDGs):SDG 7 – Affordable and Clean EnergySDG 12 – Responsible Consumption and ProductionSDG 13 – Climate ActionSDG 9 – Industry, Innovation, and Infrastructure